Ambient Pressure Photoemission Spectroscopy Reveals the Mechanism of Carbon Soot Oxidation in Ceria‐Based Catalysts. Issue 17 (27th June 2016) - Soler, Lluís; Casanovas, Albert; Escudero, Carlos; Pérez‐Dieste, Virginia; Aneggi, Eleonora; Trovarelli, Alessandro; Llorca, Jordi
Abstract: Removing soot is one of the most important challenges in minimizing the impact of combustion engines on the environment. Catalysts based on CeO2 have proved suitable to oxidize soot owing to their capacity to store and release oxygen easily while maintaining structural integrity, although their mode of operation in a complex environment involving two solid phases (catalyst and soot) and a gas phase (oxygen) is not yet fully understood. Herein, we provide a study of the surface/subsurface of ceria–soot and ceria–zirconia–soot mixtures under working conditions by means of near‐ambient‐pressure photoelectron spectroscopy. Soot abatement involves two cooperative routes: one occurring at the ceria–soot interface with formation of oxygen vacancies and Ce III and the other at the surface of soot, mediated by active superoxide species, which result from the reaction between gas‐phase O2 and oxygen vacancies. The two routes occur simultaneously and mutually reinforce each other. Abstract : A tale of two routes : Soot abatement on ceria catalysts involves two cooperative routes: one occurring at the ceria–soot interface with formation of oxygen vacancies and Ce III and the other at the surface of soot mediated by active superoxide species, which result from the reaction between gas‐phase O2 and oxygen vacancies.